2021
DOI: 10.3389/fcvm.2021.658952
|View full text |Cite
|
Sign up to set email alerts
|

Short Term Prognosis of Renal Artery Stenosis Secondary to Acute Type B Aortic Dissection With TEVAR

Abstract: Objective: To determine the effect of renal artery stenosis (RAS) resulting from acute type B aortic dissection (ATBAD) with thoracic endovascular aortic repair (TEVAR) on early prognosis in patients with ATBAD.Methods: A total of 129 ATBAD patients in the National Acute Aortic Syndrome Database (AASCN) who underwent TEVAR between 2019 and 2020 were enrolled in our study. Patients were divided into two groups: the RAS group and the non-RAS group.Results: There were 21 RAS patients (16.3%) and 108 non-RAS patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Written informed consent was obtained for all data and specimens in the database from patients or their family members. In its scale the database ranks at the forefront in China, and the data for aortic dissection cover most of the people with aortic dissection in China (Guan et al., 2022 ; Li et al., 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Written informed consent was obtained for all data and specimens in the database from patients or their family members. In its scale the database ranks at the forefront in China, and the data for aortic dissection cover most of the people with aortic dissection in China (Guan et al., 2022 ; Li et al., 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…In its scale the database ranks at the forefront in China, and the data for aortic dissection cover most of the people with aortic dissection in China (Guan et al, 2022;Li et al, 2021).…”
Section: Patient Populationmentioning
confidence: 99%
“…11 Concomitant RAS with TBAD may significantly impair renal function and lead to AKI, especially in the early stages following TEVAR. Li et al 41 showed that TBAD patients with RAS have a significantly lower mean eGFR (81.7 vs. 96.0 mL/min, p = 0.017) than those without RAS. Furthermore, they may benefit from an ancillary procedure during TEVAR to aid renal deterioration.…”
Section: Renal Diseasesmentioning
confidence: 99%
“…Finally, a recent observational study in 129 individuals that received endovascular repair for acute type B aortic dissection reported that 16.3% of the patients had RAS; these individuals had a higher incidence of AKI and lower eGFR both pre-operatively and 1-month post-operatively than individuals without RAS (81.7 ± 23.8 vs. 96.0 ± 20.0 mL/min, P = 0.017). 98 …”
Section: Thoracic Aortic Dissection and Kidney Diseasementioning
confidence: 99%